The Development of STEM-integrated LOIS Learning Unit for Enhancing Students’ Direct Current Concept Understanding - Abdurrahman, Abdurrahman; Putri, Erlita Yuani; Herlina, Kartini; Andra, Doni (FKIP Universitas Lampung, 2021)
This study developed the Science, Technology, Engineering & Mathematics (STEM)integrated Learning of Inquiry Sequences (LOIS) learning unit for students in understanding the direct current concept. Learning unit met the valid, practical, and effective criteria. The validity shows the content validity & construct validity, the practicality shows the ease of use & positive response from students, the effectivity shows the achievement of learning objectives namely improvement in understanding the direct current concept. This study used a 4-D learning unit development model namely (define, design, development, and disseminate stages). This study was included in a quasi-experiment study with one group pretest and posttest design. Data were analyzed using descriptive analysis. Based on the results, the mean of content validity was 3.76 and construct validity was 3.75 with very valid criteria. Then, the mean of the learning unit implementation in class was 0.92 and a positive response from students in the class was 0.97 with very practical criteria. Based on paired sample t-test (tcalculation = 23.291 > ttable = 2.03011) and the N-Gain value was 0.80 (high gain) showed that the LOIS learning implementation was effective to engage students in the classroom activities. Keywords: STEM-integrated LOIS learning unit, direct current, concept mastery. DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp23-34